2021
DOI: 10.1016/j.molimm.2021.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Untangling COVID-19 and autoimmunity: Identification of plausible targets suggests multi organ involvement

Abstract: Underlying mechanisms of multi-organ manifestations and exacerbated inflammation in COVID-19 are yet to be delineated. The hypothesis of SARS-CoV-2 triggering autoimmunity is gaining attention and, in the present study, we have identified 28 human proteins harbouring regions homologous to SARS-CoV-2 peptides that could possibly be acting as autoantigens in COVID-19 patients displaying autoimmune conditions. Interestingly, these conserved regions are amongst the experimentally validated B cell epitopes of SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 94 publications
0
24
0
1
Order By: Relevance
“…Several studies have reported the presence of autoantibodies in patients with coronavirus disease 2019 (COVID-19) in different frequencies: antinuclear antibodies (ANA) in 35.6%, anti-Ro/SSA in 25%, rheumatoid factor in 19%, lupus anticoagulant in 11% and antibodies against interferon (IFN)-I in 10% [ 6 , 7 , 8 , 9 ]. Moreover, 28 human proteins with homologous regions to SARS-CoV-2 peptides were identified that could potentially function as autoantigens in COVID-19 patients displaying autoimmune conditions [ 10 ]. Autoantibodies against those proteins were detected in typical autoimmune conditions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the presence of autoantibodies in patients with coronavirus disease 2019 (COVID-19) in different frequencies: antinuclear antibodies (ANA) in 35.6%, anti-Ro/SSA in 25%, rheumatoid factor in 19%, lupus anticoagulant in 11% and antibodies against interferon (IFN)-I in 10% [ 6 , 7 , 8 , 9 ]. Moreover, 28 human proteins with homologous regions to SARS-CoV-2 peptides were identified that could potentially function as autoantigens in COVID-19 patients displaying autoimmune conditions [ 10 ]. Autoantibodies against those proteins were detected in typical autoimmune conditions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 28 human proteins with homologous regions to SARS-CoV-2 peptides were identified that could potentially function as autoantigens in COVID-19 patients displaying autoimmune conditions [ 10 ]. Autoantibodies against those proteins were detected in typical autoimmune conditions [ 10 ]. Other hypothetical mechanisms include bystander activation triggered by a hyper-inflammatory state (often referred to as “cytokine storm” or “cytokine release syndrome”), viral persistence (polyclonal activation due to the constant presence of viral antigens driving immune-mediated injury) and the formation of neutrophil extracellular traps [ 1 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are known to be targeted by antibodies generated during typical autoimmune disorders, some of which have been reported to have developed after SARS-CoV-2 infection. Autoantibodies against one of these proteins, low density lipoprotein receptor 2 (LRP2), have been detected in several systemic autoimmune diseases, including SSc [ 10 ]. Such studies strongly support the theory of molecular mimicry between human and SARS-CoV-2 proteins as a mechanism leading to the development of SSc after SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…L’exposition à des épitopes viraux est une cause identifiée d’auto-immunité, précédemment avancée dans les maladies infectieuses par les coronavirus [ 3 , 4 ]. Le mimétisme moléculaire entre la protéine du Sars-CoV-2 et des protéines du « soi » a été proposé comme un facteur déclenchant auto-immun chez les patients génétiquement prédisposés [ [5] , [6] - 7 ]. En effet, la réponse immunitaire contre le Sars-CoV-2 pourrait réagir de manière croisée avec des protéines humaines qui partageraient des homologies de séquences avec le virus.…”
Section: Hypothèse Sur La Rupture De La Tolérance Et Auto-immunité Da...unclassified